Penumbuhkembangan Agribisnis Kopi Arabica Java Preanger : Dari Pangalengan Ke Pasar Dunia (Studi Kasus Di Koperasi Produsen Kopi Margamulya) - Karyani, Tuti; Djuwendah, Endah; Sadeli, Agriani Hermita; Marlina, Ima; Supriyadi, E (JURNAL AGRIBISNIS TERPADU, 2018)
Coffee is one of export commodity which planted in almost all Indonesian area. Pangalengan district is the biggest coffee production center in West Java. Farmer in this district produces, java preanger coffee, arabica coffee with a good quality and an excellent taste. Coffee agribusiness need an institutional support which help farmers to access capital and world markets. Margamulya Coffee Producer Cooperative (MCPC) is one of farmer cooperative with a lot of efforts to market their coffee to the world coffee market. The research purpose is to identify the role of MCPC in java preanger arabica coffee (JPAC) agribusiness and to formulate its growth strategy in order to encourage arabica coffee to reach at world market. The research used descriptive qualitative method with technical case study. Technical data collection is done through observation, interviews, and literature studies. The results show that MCPC has an important role in developing JPAC agribusiness in terms of assisting production facilities procurement, guidance and facilitating coffee farming productivity growth, as well as implementing the processing and marketing of coffee. Based on IFAS-EFAS analysis, the position of MCPC is in cell II, namely Growth and Build, which means the development strategy is needed through Intensive and Integration strategy. SWOT analysis represents that there are 10 main strategies will lead the MCPC to compete in the world market of coffee. Therefore, MCPC should improve professionalism in its management, attempt to increase members (coffee farmers) loyalty and build coffee agribusiness integrated with the environmental sustainable agro-tourism development.